Nitrate-barbiburate compounds inhibit matrix metalloproteinase-9 in in-vitro and in-vivo models of intestinal inflammation - O'Sullivan, Shane (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2014)
Inflammatory bowel disease is characterised by a dysregulated immune response and a compromised epithelial barrier. The enzyme matrix metalloproteinase-9 (MMP-9) is upregulated in an inflammatory setting and is believed to contribute to the pathogenesis of the disease. Nitric oxide is a gaseous signalling molecule with an, as of yet, unknown regulatory effect on MMP-9. Organic nitrates have been used as NO donors or mimetics to take advantage of NO’s pharmacological effects, but never as part of a hybrid to inhibit an MMP. The aims of my project were to synthesise and test the ability of a series of nitrate- barbiturate compounds to inhibit MMP-9 in both in-vitro and in-vivo models of intestinal inflammation and to determine the contribution of the nitrate moiety in this inhibition.
Keywords: Pharmacology, Ph.D.; Ph.D. Trinity College Dublin